THE THE INFLUENCE OF WORKING CAPITAL MANAGEMENT ON THE PROFITABILITY OF MANUFACTURING ENTERPRISES - THE CASE OF CROATIA (The South East European Journal of Economics and Business, 2023)
The aim of this research is to examine the relationship between working capital management and the profitability of Croatian manufacturing enterprises and to provide empirical evidence on the effects of working capital management on the level of profitability of manufacturing enterprises in the Republic of Croatia in the period from 2018 to 2021. The collected data were analyzed through multiple regression analysis, using a panel regression model with random effects. By analyzing panel data, the impact of receivables from customers, inventories, liabilities to suppliers, sales growth and GDP growth on the profitability of Croatian manufacturing companies was examined. The analysis of panel data examined the impact of trade receivables, inventories, payables, sales growth and GDP growth on the profitability of Croatian manufacturing enterprises. The obtained results also suggest that the variables the days sales outstanding, the days inven- tory outstanding and GDP growth are not statistically significant.